Comments on The single CCII biquads with high-inputimpedance - Abuelma’atti, M.T. (1994)
For original paper see S.-I. Liu and H.-W. Tsao, ibid., vol.38, pp.456-461 (1991). The authors comment on the configurations of the RC combinations in the circuit of Liu and Tsao. They show that the circuit can realize a high-input impedance unity gain inverter, and that by using two additional CCIIs, with their high impedance terminals grounded, it is possible to obtain two equal in magnitude and opposite in phase voltage controlled current sources. A reply by Liu is included